Propagation of Dendrobium crumenatum Sw. through In Vitro Seed Culture Using Fertilizer-Enriched and Organic Complex Media - Su'udi, Mukhamad; Ziyaroh, Putry Lazimatu (Life Science and Biotechnology, 2024)
Dendrobium crumenatum Sw. is one of the epiphytic orchids with high ecological and economic value. This study aims to examine the effect of media containing organic compounds enriched with fertilizers for in vitro propagation of D. crumenatum seeds. This culture medium contains organic materials such as potatoes, bananas, coconut water, charcoal, sucrose, and foliar fertilizer. This medium was designed to provide macro, micro, and growth hormone nutrients that support explant growth. The research procedure included sterilization of orchid seeds, explant sowing, and growth observation for about two months. The results showed that orchid seeds experienced optimal growth in media with the addition of coconut water and other organic compounds. The formulation of organic-based media with the addition of coconut water and other supporting compounds is effective in supporting the in vitro growth of orchids, providing opportunities for efficient propagation of orchid species. Explant growth reached 1-2 cm at the 68th day after sowing, with a fresh green colour as an indicator of optimal physiological conditions. The even distribution of shoots indicates that the media provides sufficient space and nutrients without competition between explants. In sum, simple tissue culture media produced from a mixture of organic materials proved reliable function and suited for growing D. crumenatum orchid seeds to produce plantlets, and into further extent it would support conservation efforts. Key words: Conservation, organic materials, pigeon orchid, simple media, tissue culture